Witches, fire, and fairies: Parent–child conversations during fantastic and real emotionally charged stories. Issue 6 (20th September 2018) - Carrick, Nathalie; Sawaya, Stephanie; Palisoc, Jennifer
Abstract: Preschoolers' fantasy–reality distinctions vary by the emotional content of the information; they report that happy and sad fantastic or real events can occur more often than frightening events. Given that children rely on parents' testimony when evaluating information, the present study examined the role parents play in children's fantasy–reality distinctions for emotionally charged events. Fifty‐nine parents and their 3‐ to 5‐year‐olds read happy, frightening, and sad stories that contained either fantastic or real events. Conversations during the readings were coded and analysed for patterns across story conditions. Findings reveal that topics of conversations differed significantly by discrete emotion and at times by reality status. Parents and children engaged with happy and sad events (e.g., by relating events to children's lives and helping the story characters) and distanced themselves from frightening events (e.g., by ameliorating the situation and switching negative tone to positive). Findings provide new insights into how parents talk to children about emotionally charged fantasy and reality that contribute to our understanding of how children construct their understanding of real and unreal information. Highlights: The study examined parent–child conversations about happy, frightening, and sad fantastic and real events. While reading stories, parents and children interacted with the happy and sad events and distanced themselves from the frightening events. Conversations about fantasy and reality may influence children's fantasy–reality distinctions.